2013
DOI: 10.1186/1999-3110-54-6
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory activities of acteoside, isoacteoside, and its structural constituents against protein glycation in vitro

Abstract: BackgroundAdvanced glycation end products (AGE) are substances that can induce insulin resistance in adipocyte, hepatocyte and muscle cells. This resistance correlates highly with cardiovascular disease and diabetic complications. Acteoside (A), a phenylethanoid glycoside, is an active compound in several plants and traditional herbal medicines. Acteoside, its structural isomer, isoacteoside (I), and their constituents, caffeic acid (C) and 3,4-dihydroxyphenylethanol (D), were used in the study to investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…Of the compounds, acteoside ( P5 ) and isoacteoside ( P6 ) had high DPPH radical scavenging activity, ORAC activity, and inhibitory activity of BSA glycation, while iridoids ( I1 , I2 and I3 ) had no antioxidant and antiglycation activities. There are plenty of reports on the antioxidant and antiglycation activities of the compounds identified in this study, particularly acteoside and isoacteoside [ 27 32 ], and the activities we observed were almost similar to previous reports. Given the amount present of the compounds and their activities, acteoside ( P5 ) makes a major contribution to the antioxidant and antiglycation activities of young sesame leaves.…”
Section: Resultssupporting
confidence: 89%
“…Of the compounds, acteoside ( P5 ) and isoacteoside ( P6 ) had high DPPH radical scavenging activity, ORAC activity, and inhibitory activity of BSA glycation, while iridoids ( I1 , I2 and I3 ) had no antioxidant and antiglycation activities. There are plenty of reports on the antioxidant and antiglycation activities of the compounds identified in this study, particularly acteoside and isoacteoside [ 27 32 ], and the activities we observed were almost similar to previous reports. Given the amount present of the compounds and their activities, acteoside ( P5 ) makes a major contribution to the antioxidant and antiglycation activities of young sesame leaves.…”
Section: Resultssupporting
confidence: 89%
“…Literature reports on anti‐diabetic related effects of phenylpropanoids and iridoids, such as the decrease of advanced glycation end‐products, the improvement of insulin sensitivity, and glycogen phosphorylase‐a as target of these compounds (Liu et al ., ; Vaidya et al ., ). Acetylharpagide, an iridoid glycoside present in Leonurus sibiricus , decreased the blood glucose levels of alloxan‐induced diabetic mice by 29% after 2 h of treatment (Ahmed et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…The fluorescence detection (340–370 nm for excitation and 420–470 nm for emission) for AGE formation was frequently used in the literature 24,25. ML is one of the well-characterized AGEs;7 however, detection of nonfluorescent CML is mainly performed by liquid chromatography–mass spectrometry (LC/MS),27 LC/MS/MS,28 ELISA, and/or immunostains 19,20. In this study, the fluorescence measurement and detection of CML formation in the BSA/Gal models were done using two independent methods; acetH showed promising antiglycation results and was further used to investigate CML formation by Western blot assays.…”
Section: Resultsmentioning
confidence: 99%